Decomposition and Nitrogen Release Dynamics of Fruit Tree Leaf Litters in Arid Western Rajasthan - Soni, M L; Yadava, N D; Bhardwaj, S (Annals of Arid Zone, 2016)
Decomposition and nitrogen (N) release dynamics of leaf litters of Citrus aurontifolia, Aegle marmelos and Cordia myxa were studied from June 2010-April 2011 at Research Farm of Central Arid Zone Research Institute, Regional Research Station, Bikaner (Rajasthan). Among the three species, leaf litter of C. aurontifolia decomposed more rapidly followed by those of A. marmelos and C. myxa. About 51% of C. aurontifolia, 34% of A. marmelos and 21% of C. myxa litter disappeared in surface and 59% of C. aurontifolia, 36% of A. marmelos and 24% of C. myxa disappeared in buried condition within 60 days. The decomposition pattern of all the three species could be divided into two phases. The first phase (rainy season from June to November) showed a relatively faster decomposition rate (R) while the second phase (dry and cold season from November to April) showed relatively slower decomposition. The N release in both surface and buried condition followed the order C. aurontifolia>Aegle marmelos>Cordia myxa. The N release in C. aurontifolia, A. marmelos and C. myxa during the cropping season (July to October) was 54.1, 47.6 and 11.4% in surface applied litter and 70.5, 54.7 and 23.1% in buried condition, respectively. The slowest N release was observed in C. myxa due to its higher lignin content (45.5%) as compared to C. aurontifolia (19.8%) and A. marmelos (15.4%). Key words: Aegle marmelos, Citrus aurontifolia, Cordia myxa, litter decomposition, nitrogen release.